The true story of Stellina - Pericoli, Matteo, 1968- (Alfred A. Knopf, 2006)
The true story of a baby finch rescued and raised by the author and his wife. Stellina was a bird: "Cheep", a very little bird: "Cheep!" So begins critically acclaimed author Matteo Pericoli's all-true story of how he and his wife, Holly, came to rescue and raise a little finch, Stellina, in the middle of New York City. When no zoo would take the abandoned bird, fallen from her nest onto a busy street, Holly took her home and gave her the best life she could. And there, in a Manhattan apartment, Stellina leaned how to eat, fly, and sing.